From ‘to die a tribe and be born a nation’ towards ‘culture, the foundation of a nation’: the shifting politics and aesthetics of Namibian nationalism (Journal of Namibian Studies : History Politics Culture, 2015)
Namibia’s postcolonial nationalist imaginary is by no means homogeneous. Overall, however, it is conspicuous that as Namibia celebrates her twenty-fifth anniversary of independence, national identity is no longer defined primarily through the common history of the liberation struggle but through the tolerant accommodation, even wholehearted celebration, of cultural difference. This article attempts to understand the shifting politics and aesthetics of Namibian nationalism from two interconnected angles. On the one hand, it takes a historical perspective; it looks into shifting discourses and practices of nationalism over the past century, starting from the anti-colonial resistance at the turn to the 20th century through to the twenty-fifth anniversary of Namibian independence. On the other hand, the article investigates the cultural redefinition of the bonds between the Namibian people(s), which has been a significant aspect of the constructions of postcolonial Namibian nationhood and citizenship. The argument highlights urban social life and cultural expression and the links between everyday life and political mobilization. It thereby emphasizes the nationalist activism of the developing Black urban culture of the post-World War II era and the internal urban social movements of the 1980s.